Взаимодействие поставщика и потребителя IT-сервисов информационной системы управления предприятием - Евланов, М. В. (ХНУРЭ, 2011)
This paper considers the problem of formalized representation of interaction between providers and consumers of IT-services in the establishment and operation of the service-oriented enterprise information management systems. The paper proposed to consider the basic concept of this relationship as a kind of concept of customer relationship management. For a formalized description of the relationship of the provider and consumer IT-services in the proposed mathematical apparatus noncooperative games. These differences submission noncooperative game provider and consumer IT-services at different stages of the life cycle of a service-oriented information system.